2010
DOI: 10.1007/s10926-009-9224-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Work Participation and Work Functioning in Depressed Workers: A Systematic Review

Abstract: Background Depression is associated with negative work outcomes such as reduced work participation (WP) (e.g., sick leave duration, work status) and work functioning (WF) (e.g., loss of productivity, work limitations). For the development of evidence-based interventions to improve these work outcomes, factors predicting WP and WF have to be identified. Methods This paper presents a systematic literature review of studies identifying factors associated with WP and WF of currently depressed workers. Results A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
237
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(272 citation statements)
references
References 78 publications
20
237
3
3
Order By: Relevance
“…It is apparent that common mental disorders have significant effects on general wellbeing and ability to work, also expressed in terms of reduced work functioning and loss of productivity, and difficulties in meeting the various demands at work [5,49]. This is supported by the comparably longer periods of sick leave among sick-listed individuals with common mental disorders, compared with several other disorders [7]. However, in spite of the broad battery of health measures, self-rated work ability proved to have the strongest association with RTW among health-related measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is apparent that common mental disorders have significant effects on general wellbeing and ability to work, also expressed in terms of reduced work functioning and loss of productivity, and difficulties in meeting the various demands at work [5,49]. This is supported by the comparably longer periods of sick leave among sick-listed individuals with common mental disorders, compared with several other disorders [7]. However, in spite of the broad battery of health measures, self-rated work ability proved to have the strongest association with RTW among health-related measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report differences in the period of time until RTW, when comparing different diagnoses [3,4]; the longest sick leave is reported in connection with depression [7] and anxiety [16,17]. Duration and severity of health problems before becoming sick-listed also affects time to RTW [16].…”
Section: Predictors Of Return To Work (Rtw)mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review 40 reported high absentee rates and reduced productivity at work in this population. Although they did not refer exclusively to HCV patients, Lagerveldet al 41 reinforced the association between the duration of a depressive episode and the incapacity for work, regardless of the severity of this disorder. These data highlight the need to identify and treat depressive symptoms at an early stage, thus improving the well-being of these individuals and preventing their occupational lives from being compromised.…”
Section: Prevalence Of Depressive Symptoms and Harmful Alcohol Usementioning
confidence: 99%
“…Based on prospective studies, increases in job control, social support, and communication in the working place are promising candidates to decrease the risk for disability pension (7-9). However, intervention studies related to work-related factors to prevent mental disorders among aging workers are very few (10,11).…”
Section: Is Retirement Beneficial or Harmful To Mental Health?mentioning
confidence: 99%